Analisis Kinerja Keuangan Badan Perencanaan Pembangunan Daerah (BAPPEDA) Provinsi Aceh - A. Chalil Gibran; Batubara, Chuzaimah; Nurwani (Ali Institute of Research and Publication, 2023)
This research aims to determine the extent of shopping compatibility at Bappeda of Aceh Province during 2017-2021 based on analysis of direct and indirect expenditure growth at Bappeda of Aceh Province during 2017-2021. This research method used is descriptive quantitative with data collection techniques through documentation. The subjects of this study are the parties involved in the research that is the Head of Finance Section of the Bappeda Aceh Province. The object of this study is the Financial Performance of Bappeda Aceh Province by looking at the Budget Realization Report (LRA) for five fiscal years during 2017-2021. The result of the study indicate that the compatibility of direct and indirect spending during 2017-2021 is categorized as good. This is because the percentage of direct compatibility during 2017-2021 is greater than the percentage of indirect spending. The biggest decrease in testing direct spending on total spending is in 2019 which is 61%. The lowest percentage in the indirect analysis of total spending is in 2021, which is 34%. The growth of spending with the fiscal years during 2017-2021 is positive or negative. The results of the analysis on the growth of spending in 2017-2018 was positive of 12%. Furthermore, in 2018-2019 it was negative of -3%, in 2019-2020 it was positive of 3%, and in 2020-2021 it was positive of 1%.